2014
DOI: 10.1080/01431161.2014.951742
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of atmospheric correction models and Landsat surface reflectance product in an urban coastal environment

Abstract: Precise atmospheric correction is important for applications where small differences in surface reflectance (SR) are significant, such as biomass estimation, crop phenology, and retrieval of water quality parameters. It also enables direct comparison between different image dates and different sensors. As a precursor to monitoring different parameters of water quality around the coastline of Hong Kong using medium-resolution sensors Landsat TM/ETM, and HJ-1A/B, this study evaluated the performance of five atmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
62
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 147 publications
(75 citation statements)
references
References 30 publications
5
62
1
2
Order By: Relevance
“…This finding is similar to that reported by Nazeer et al [68], who observed that, among five algorithms tested, 6S produced the smallest difference in field-measured surface reflectance and that obtained using the Landsat ETM sensor.…”
Section: Discussionsupporting
confidence: 81%
“…This finding is similar to that reported by Nazeer et al [68], who observed that, among five algorithms tested, 6S produced the smallest difference in field-measured surface reflectance and that obtained using the Landsat ETM sensor.…”
Section: Discussionsupporting
confidence: 81%
“…To address inconsistencies among image datasets, Landsat TM images were geo-rectified against the Landsat OLI images, and then all images were projected onto the Albers equal-area conic coordinate system to accurately extract land cover area. A module in ENVI software [40], i.e., the FLAASH module was used Sustainability 2018, 10, 188 4 of 18 for atmospheric corrections of Landsat images [41]. The point layers, including the center positions of cities, counties, towns and villages, and the polygon layers of different levels of administrative boundaries from the Resource Environmental Science Data Center of Chinese Academy of Sciences (http://www.resdc.cn) and National Earth System Science Data Sharing Infrastructure, National Science and the Technology Infrastructure of China (http://www.geodata.cn) were also used in this study.…”
Section: Data Sources and Preprocessingmentioning
confidence: 99%
“…We used FLAASH (Fast Line-of-Sight Atmospheric correction model Analysis of Spectral Hypercubus) for atmospheric correction [40]. All of the above steps were completed in ENVI5.2 software.…”
Section: Satellite Image Preprocessingmentioning
confidence: 99%